Enabling real-time collaborative decision-making between airport and surface transport operations - Jimenez, Edgar; Blasco-Puyuelo, Juan; Alcolea, Ruben; Salamanca, Raquel; Rothe, Henrik; Moxon, Rich (Elsevier, 2023)
Current developments in collaborative decision-making in the air transport context are restricted to airport and air traffic management operations and stakeholders, disregarding the relevance of airport access and egress in the door-to-door journey for passengers. This paper summarises the IMHOTEP (Integrated Multimodal Airport Operations for Efficient Passenger Flow Management) concept of operations, which extends Airport Collaborative Decision-Making implementations by incorporating surface access. Enhanced situational awareness achieved by extending the monitoring of passenger flows beyond the airport boundaries improve resource allocation and last-minute capacity utilization. It also facilitates the identification of passenger connectivity requirements in terms of links to ground services.
Keywords: Data sharing and ownership; Inter-modality; Innovative hubs; Sustainable and integrated airports; Reliable and seamless connectivity for passengers